A Flexible Calibration Approach for Cameras with Double-Sided Telecentric Lenses. (5th May 2016) - Yao, Linshen; Liu, Haibo
With their constant perspective and large magnification in the working distance, double-sided telecentric lenses have been widely used in machine-vision applications. This paper puts forward a flexible calibration approach for the double-sided telecentric camera. Based on an orthographic projection model considering the major sources of lens distortions, a two-step calibration procedure is proposed. In this approach, the camera parameters apart from the lens distortions are achieved by a closed-form solution. Then a double non-linear optimization is performed to refine all the parameters, including the distortion coefficients and distortion centre. In addition, to achieve a flexible calibration procedure, the calibration pattern used is a cheap print product rather than a professional customized calibration pattern. Simulation and real-world experiments are performed to validate the performance of the proposed calibration approach. In addition, the comparison experiments between the print calibration pattern and professional calibration pattern are carried out, and the accuracy of calibration results are at the same level.